A New Strategy to Improve Alkyd/Acrylic Compatibilization in Waterborne Hybrid Dispersions - Goikoetxea, Monika (2010)
Grafting of alkyd resin to the acrylic polymer is needed to fully exploit the possibilities of these hybrids; but in the current technology, grafting is accompanied by an important reduction of the unsaturated groups of the alkyds, which adversely affects the curing of the film and its properties. A novel strategy that overcomes these limitations is presented. The strategy is based on the use of alkyd resin functionalized with methacrylic groups, that substantially improved the incorporation of the resin to the growing acrylic polymer chain, and the polymer particle homogeneity, without decreasing the degree of unsaturation in the alkyd resin.